Island of grass - Wohl, Ellen, author; University Press of Colorado, publisher (Colorado State University. Libraries, 2009)
Island of Grass tells the story of the Cathy Fromme Prairie Natural Area, a 240-acre preserve surrounded by housing developments in Fort Collins, Colorado. This small grassland is a remnant of the once-vast prairies of the West that early European explorers and settlers described as seas of grass. Agricultural land use and urban expansion during the past two centuries have fragmented and altered these prairies. All that remains today are small islands.
The greater context -- The sea of grass -- Islands and archipelagos -- The Fromme Prairie -- Grassroots -- Life among the leaves of grass -- Keystone of the shortgrass prairie -- Hunters of the grasslands -- On the prairie winds.
Keywords: Prairie ecology -- Colorado -- Fort Collins Region; Natural history -- Colorado -- Fort Collins Region; Cathy Fromme Prairie (Colo.)